SOSIALISASI MANAJEMEN LITERASI WAKAF UANG PADA REMAJA MASJID DI DAERAH GUWOSARI - Rusny Istiqomah Sujono; Baiq Ismiati; Febrian Wahyu Wibowo; Mu’inan Rafi; Ahmad Yunadi; Muhammad Dimas Setiawan (Universitas Mataram, 2022)
Waqf is one of the distribution tools in Islam, so if it is optimized properly it can help the regional economy. Based on the survey results, waqf literacy in Indonesia is still in the low category and this correlates with the low collection of cash waqf in Indonesia. The mosque is a place to collect social funds and all mosque activities are coordinated with the mosque takmir and mosque youth. Therefore, youth mosques in the Guwosari area need to be given socialization of cash waqf literacy management so that the collection of cash waqf in the Guwosari regional mosques can increase and help the regional economy. The general purpose of holding this activity is to increase literacy of cash waqf. The specific goal is for mosque youth to know the direct benefits of cash waqf for the people, know the flow of its implementation, the importance of cash waqf and increase awareness of cash waqf. The method used is lectures and socialization of cash waqf literacy management to mosque youth by providing material from several parties who are very understanding about cash waqf literacy management. The result of this activity is that mosque youth have an account to collect cash waqf in the mosque to be deposited into LKS-PWU and there are some who already have experience in collecting. In addition, based on the results of the evaluation, these activities were carried out well, where mosque youths received literacy related to cash waqf as a whole from the basics to the collection process which can be said to have increased in terms of literacy. So that it is hoped that there will be other ongoing activities, namely monitoring the program for collecting cash waqf, so that the collection of cash waqf can run more optimally.